Time to clinically relevant fracture risk scores in postmenopausal women - Gourlay, Margaret L. (Am J Med, 2017)
BACKGROUND: Clinical practice guidelines recommend use of fracture risk scores for screening and pharmacologic treatment decisions. The timing of occurrence of treatment-level (according to 2014 National Osteoporosis Foundation guidelines) or screening-level (according to 2011 US Preventive Services Task Force guidelines) fracture risk scores has not been estimated in postmenopausal women. METHODS: We conducted a retrospective competing risk analysis of new occurrence of treatment-level and screening-level fracture risk scores in postmenopausal women aged 50 and older, before receipt of pharmacologic treatment and before first hip or clinical vertebral fracture. RESULTS: In 54,280 postmenopausal women aged 50 to 64 without a bone mineral density test, the time for 10% to develop a treatment-level FRAX® could not be estimated accurately because of rare incidence of treatment-level scores. In 6096 women who had FRAX scores calculated with bone mineral density, the estimated unadjusted time to treatment-level FRAX ranged from 7.6 years (95% CI, 6.6, 8.7) for those aged 65 to 69 to 5.1 years (95% CI, 3.5, 7.5) for those aged 75 to 79 at baseline. Of 17,967 women aged 50 to 64 with a screening-level FRAX at baseline, 100 (0.6%) experienced a hip or clinical vertebral fracture by age 65. CONCLUSIONS: Postmenopausal women with sub-threshold fracture risk scores at baseline were unlikely to develop a treatment-level FRAX score between ages 50 and 64. After age 65, the increased incidence of treatment-level fracture risk scores, osteoporosis and major osteoporotic fracture supports more frequent consideration of FRAX and bone mineral density testing.